ADMINISTRATION OF EXPERIMENTAL ACTIVITIES AT THE SECONDARY EDUCATIONAL INSTITUTIONS IN THE CONTEXT OF EDUCATIONAL CHANGES - Liudmyla Ilich; Alla Panchenkо; Olena Akilina; Lizunova Olena (Borys Grinchenko Kyiv Metropolitan University, 2022)
Theoretical principles of administration of experimental activities at the secondary educational institutions are distinguished in the article in three dimensions such as: a part of innovative activities, projects administration as well as theoretical and methodical direction of an educational institution existence. Ukrainian and foreign experience in administrative organisation of experiments at the secondary educational establishments is outlined with the aim to improve their activities as a long-term run taking educational innovations and school needs diagnostics into consideration. The article reveals the peculiarities of functioning and administration at Kyiv Lyceum «Prestizh» which has been a school-lab for quality inspection of implementation of innovative educational technologies in the fields of Mathematics, Physics and IT of Institute of Pedagogy of the NAES of Ukraine since 2018. The Lyceum has become an experimental platform at All-Ukrainian level dealing with the topic «Conceptual Foundations of Creation of Educational Engineering Environment at Kyiv Lyceum «Prestizh». The Lippitt-Knoster Model and Canvas have been used for studying the state of the administration of experimental activities as a part of educational changes. It is researched that the administration of experimental activities at the Lyceum consists of administration about separate projects. The project «I am a researcher» has become one of them. Its aim is to integrate mathematical education with the English language learning. The implementation of the research has been carried out with the usage of IT, STEM-technologies as well as CLIL methodology (Content and Language Integrated Learning) in educating. The possibility to integrate studying a language with other subjects and adopt the administrative methods (the combination of «Six Sigma» and «Scrum») have been justified. Due to the fact that all the transformations at an educational institution should be followed by every interested participant, personal vision of involving teachers, opportunities and pedagogical leadership capability has been offered. The results of involving teachers into experimental activities can become as positive experience for other secondary educational establishments.